Injuries and Strength Training Practices in Collegiate Tennis - Ecaterina Vasenina; William B. Hammert; Ryo Kataoka; Scott J. Dankel; Samuel L. Buckner (MDPI AG, 2022)
Strength and conditioning practices may influence injury rates in the sport of tennis. Methods: Coaches reported the number injuries over the past year. Coaches were also surveyed on whether their training program included training related to upper-body or lower-body strength, power, muscle growth, and eccentric exercise. Separate regression analyses were run in the upper and lower body to examine the relationship between injuries and participation in training focused on strength, power, growth, and maximal eccentric exercise. A total of 111 coaches were surveyed. The most frequent injuries observed were ankle sprains (144 injures), followed by paraspinal muscle strains (126 injuries). When pooled, there were a total of 355 lower-body and 260 upper-body injuries. Strength and conditioning practices explained 9.9% of the variance of injury rates in the upper body (R2 = 0.099). The only significant predictor of upper-body injury was participation in upper-body muscle growth training (β = 1.613, p = 0.013). In addition, training practices explained 11.1% of the variance of injury in the lower body (R2 = 0.111). Coaches value injury prevention exercise, sports-specific training and flexibility and mobility training the most, with muscle growth and maximal power ranked lowest. Additionally, the most frequent injuries observed in collegiate tennis players were ankle sprains (144 injures), followed by paraspinal muscle strains (126 injuries).